A SYSTEMATIC LITERATURE REVIEW: THE IMPACT OF PROJECT-BASED LEARNING MODEL IMPLEMENTATION ON HIGH SCHOOL STUDENTS' LEARNING OUTCOMES ASSESSED THROUGH VOSViewer IN THE GOOGLE SCHOLAR DATABASE - Trustha Cinantya Putri Tulungagung (Jurnal Pelita Pendidikan, 2023)
Education involves the dynamic exchange between educators and students in the instructional context. Conversely, project-based learning represents an instructional paradigm that integrates projects into the learning journey, with these projects encompassing both individual and group undertakings. Collaboratively pursued within defined temporal boundaries, such projects culminate in concrete outcomes. This study seeks to investigate the potential impact of project-based learning approaches on the participation of secondary school students. The systematic literature review method is employed to comprehensively evaluate existing research in this domain. By exploring the effects of project-based learning, the study sheds light on its role in enhancing student engagement and learning outcomes. This investigation contributes to the ongoing discourse on innovative pedagogical strategies and their efficacy in the context of modern education.